2016
DOI: 10.1111/mec.13563
|View full text |Cite
|
Sign up to set email alerts
|

Species‐wide patterns of DNA methylation variation in Quercus lobata and their association with climate gradients

Abstract: DNA methylation in plants affects transposon silencing, transcriptional regulation and thus phenotypic variation. One unanswered question is whether DNA methylation could be involved in local adaptation of plant populations to their environments. If methylation alters phenotypes to improve plant response to the environment, then methylation sites or the genes that affect them could be a target of natural selection. Using reduced-representation bisulphite sequencing (RRBS) data, we assessed whether climate is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
168
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 81 publications
5
168
1
1
Order By: Relevance
“…Many studies have quantified epigenetic variation by applying standard statistical measures used in population genetics (Box 3). To provide conclusive evidence that epigenetic variation can result in ecologically relevant phenotypic changes that are autonomous from genotypic variation, we suggest that future studies of pure epigenetic variation could transplant different populations into common environments, and test for the contributions of genetic effects to epigenetic variation by testing for genome-or epigenome-wide associations in sample individuals and their offspring (GWAS and EWAS, respectively), after correcting for confounding by genetic background using a kinship matrix (Dubin et al, 2015;Orozco et al, 2015;Lea et al, 2016;Gugger et al, 2016). Several recent studies have also developed statistical approaches to partition environmental and genetic effects on epigenetic variation.…”
Section: The Evolutionary Potential Of Epigenetic Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have quantified epigenetic variation by applying standard statistical measures used in population genetics (Box 3). To provide conclusive evidence that epigenetic variation can result in ecologically relevant phenotypic changes that are autonomous from genotypic variation, we suggest that future studies of pure epigenetic variation could transplant different populations into common environments, and test for the contributions of genetic effects to epigenetic variation by testing for genome-or epigenome-wide associations in sample individuals and their offspring (GWAS and EWAS, respectively), after correcting for confounding by genetic background using a kinship matrix (Dubin et al, 2015;Orozco et al, 2015;Lea et al, 2016;Gugger et al, 2016). Several recent studies have also developed statistical approaches to partition environmental and genetic effects on epigenetic variation.…”
Section: The Evolutionary Potential Of Epigenetic Variationmentioning
confidence: 99%
“…Several recent studies have also applied next-generation sequencing techniques to simultaneously analyse the relationships between genetic variation, epigenetic variation, and the environment (e.g. Schmitz et al, 2011;Platt et al, 2015;Gugger et al, 2016). In these studies, genomic DNA treated with sodium bisulphite was sequenced.…”
Section: How Stable Is Transgenerational Epigenetic Variation?mentioning
confidence: 99%
“…While the structure of B1 and B2 can only be shaped through natural selection, B3 could be direct changed by the environment. The epigenetic differentiation was observed in contrast habitats without variation differentiation (Foust et al., 2016; Gugger et al., 2016; Lira‐Medeiros et al., 2010; Schulz et al., 2014), but it remained unexplored how stable and inheritable the B3 variation is in these studies. Common garden filtered the plastic B3 variation in our study, and epigenetic divergence between populations in the introduced region and in its original region was weakened.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic diversity can generate massive heritable variation of ecologically relevant plant traits such as root allocation, drought tolerance and nutrient plasticity (Zhang, Fischer, Colot, & Bossdorf, 2013), and it appears to increase the productivity and stability of plant populations in Arabidopsis thaliana under artificial conditions (Latzel et al., 2013). An increasing number of studies have also demonstrated the common existence and significant role of epigenetic variation in plant populations of herbs (Foust et al., 2016; Herrera, Medrano, & Bazaga, 2014; Medrano et al., 2014; Preite et al., 2015; Schulz, Eckstein, & Durka, 2014), shrubs (Avramidou, Ganopoulos, Doulis, Tsaftaris, & Aravanopoulos, 2015; Herrera & Bazaga, 2013, 2016), and trees (Guarino, Cicatelli, Brundu, Heinze, & Castiglione, 2015; Gugger, Fitz‐Gibbon, PellEgrini, & Sork, 2016; Lira‐Medeiros et al., 2010; Platt, Gugger, Pellegrini, & Sork, 2015; Sáez‐Laguna et al., 2014) under natural conditions. Therefore, epigenetic variation can be a very important mechanism for invasive plant success in a broad range of environments (Douhovnikoff & Dodd, 2014; Richards, Schrey, & Pigliucci, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The recent application of molecular techniques to ecological questions has revealed that epigenetic regulatory mechanisms, such as DNA methylation, may respond dynamically and independently to sudden changes in the environment (e.g., Gugger, Fitz‐Gibbon, Pellegrini, & Sork, 2016; Trucchi et al., 2016). Although there are several epigenetic mechanisms that can alter gene expression (e.g., chromatin remodeling, histone modifications, small interfering RNAs), DNA methylation of cytosines is the most widely studied (Schrey et al., 2013; Verhoeven, Vonholdt, & Sork, 2016) and can have important ecological effects.…”
Section: Introductionmentioning
confidence: 99%